2020
DOI: 10.1177/1470320319900039
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene insertion/deletion polymorphism and high-altitude pulmonary edema: An updated meta-analysis

Abstract: Objective: The purpose of the study was to investigate the association between angiotensin-converting enzyme gene insertion/deletion polymorphism and high-altitude pulmonary edema. Methods: A systematic search for relevant literature was performed in MEDLINE, CNKI, and EMBASE. The pooled odds ratios and their corresponding 95% confidence intervals were calculated in STATA 12.0 software. Results: Seven studies, with a total of 304 patients and 564 controls, qualified for the inclusion in the analysis. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…To date, a number of genes associated with susceptibility to HAPE have been identified, including angiotensinconverting enzyme (ACE), [12][13][14] endothelial nitric oxide synthase (eNOS), 15,16 angiotensin (AGT) and its receptor (AGTR1), 17 heat-shock protein 70 (HSP70), 18 HLA, 19 mitochondrial DNA (mtDNA), 26 aldosterone synthase (CYP11B2), 16 endothelin-1 (ET-1), 12 pulmonary surfactant-associated protein A1 (SP-A1) and A2 (SP-A2), 27 and β2 adrenergic receptor (ADRB2). 28,29 However, few studies have investigated the association between the genetic characteristics of steroid hormone metabolism genes and HAPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a number of genes associated with susceptibility to HAPE have been identified, including angiotensinconverting enzyme (ACE), [12][13][14] endothelial nitric oxide synthase (eNOS), 15,16 angiotensin (AGT) and its receptor (AGTR1), 17 heat-shock protein 70 (HSP70), 18 HLA, 19 mitochondrial DNA (mtDNA), 26 aldosterone synthase (CYP11B2), 16 endothelin-1 (ET-1), 12 pulmonary surfactant-associated protein A1 (SP-A1) and A2 (SP-A2), 27 and β2 adrenergic receptor (ADRB2). 28,29 However, few studies have investigated the association between the genetic characteristics of steroid hormone metabolism genes and HAPE.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the polymorphisms of these enzymes are associated with a variety of diseases. 11 Although many genetic association studies have identified dozens of genes associated with susceptibility to HAPE, [12][13][14][15][16][17][18][19] few studies have reported a relationship between the genetic characteristics of steroid hormone metabolism genes and HAPE. Thus, in this study, we conducted a casecontrol association analysis to investigate the correlation between seven steroid hormone metabolism genes (STAR, HSD3B1, HSD3B2, CYP17A1, CYP21A2, CYP11B1, and CYP11B2) and HAPE in a Chinese Han population (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of performing meta-analysis studies is to confirm the statistical procedure of the combined data of the global studies and also based on single study results, the utility of an intervention of a hypothesis cannot be done (Haidich, 2010), and it has been proven by an enormous number of meta-analysis studies. ACE gene polymorphism has been implemented the meta-analysis studies in almost all the human diseases and showed both the effects of association (Ahmad et al, 2019;Aslbahar et al, 2018;Han et al, 2017;Luo et al, 2016;Mengesha et al, 2019;Xu et al, 2018;Yuan et al, 2017;Zheng and Huang, 2020). However, there are no meta-analysis studies have been documented due to the limited number of global studies have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Each genotype is characterized by varying plasma concentrations of ACE, with II exhibiting low levels, ID displaying medium levels, and DD demonstrating high levels. [36][37][38][39] This disparity in ACE concentration has been established through Baudin's study, which reported serum ACE concentrations of 240 μg/L, 330 μg/L, and 365 μg/L for genotypes II, ID, and DD, respectively. 35 Interestingly, the concentration of angiotensin II does not align with the ACE concentration, as it measured 11.0, 8.6, and 9.9 μg/L for II, ID, and DD, respectively.…”
Section: The Ace I/d Gene Polymorphismmentioning
confidence: 99%
“…However, it demonstrates a compelling association with the plasma concentration of ACE, underscoring the substantial impact of the ACE I/D gene polymorphism on the regulatory mechanisms governing ACE expression at the systemic level. 6, [35][36][37][38][39] The ACE I/D gene polymorphism produces two alleles, namely the insertion allele (I) and the deletion allele (D), resulting in three genotypes: II, ID, and DD. Each genotype is characterized by varying plasma concentrations of ACE, with II exhibiting low levels, ID displaying medium levels, and DD demonstrating high levels.…”
Section: The Ace I/d Gene Polymorphismmentioning
confidence: 99%